Analisis kesulitan pemecahan masalah matematika berdasarkan teori Polya pada peserta didik kelas IV sekolah dasar - Winny Arsyabinta; Anesa Surya; Retno Winarni (Didaktika Dwija Indria, 2023)
This reseacrh aims at explaining and describing the difficulty of mathematics problem solving based on Polya theory to the 4th grade students of elementary school. This research is a qualitative descriptive research with a case study approach. Sampling was done with research subjects. Data collection was carried out using passive participatory observation techniques, in-depth interviews, and documentation studies. The technique to test validity data is using method triangulation and source triangulation. Data analysis uses the Creswell model technique The results of this study are the difficulties that occur in students in solving problems including: (1) understanding the concept of flat shapes when changed into word problems; (2) writing information that is known and asked about; (3) misconceptions about story problems; (4) determining the solution to the problem to be used; (5) problem-solving plans are not by the questions; (6) description of how to do things that are not systematic; (7) writing methods that do not use known, asked, answered, and conclusions; (8) completeness of problem-solving answers; (9) writing units of length and conclusions; (10) attention to the little things in detail that lead to errors.